The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1155/2011/273105
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Erythrocyte Sedimentation Rate, White Blood Cell Count, Liver Enzymes, and Magnesium after Gastric Bypass Surgery

Abstract: Background. Roux-en-Y gastric bypass (RYGBP) is an established method for treatment of obesity, a condition of chronic inflammation with liver steatosis, characterised by increased erythrocyte sedimentation rate (ESR), white blood cell count (WBC), liver enzymes, and decreased magnesium (Mg). We investigated alterations, if any, in ESR, WBC, alanine aminotransferase (ALT), gamma-glutamyl transferase (GGT), and Mg after RYGBP. Methods. 21 morbidly obese nondiabetic patients who underwent RYGBP surgery were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
5
1
Order By: Relevance
“…The clinical literature about effects of bariatric surgery on hematopoiesis is limited. Several reports show a decrease of total WBC and neutrophil numbers 1 year after RYGB (41)(42)(43), while there is one report suggesting that WBC and neutrophil numbers decreased 30 days after VSG (44). Although we observed a decrease of WBC and neutrophil numbers in the lean mice after VSG over time, the proportion of neutrophils is persistently higher than in sham mice.…”
Section: Vsg Causes Bone Loss Through Mechanisms Independent Of G-csfcontrasting
confidence: 68%
“…The clinical literature about effects of bariatric surgery on hematopoiesis is limited. Several reports show a decrease of total WBC and neutrophil numbers 1 year after RYGB (41)(42)(43), while there is one report suggesting that WBC and neutrophil numbers decreased 30 days after VSG (44). Although we observed a decrease of WBC and neutrophil numbers in the lean mice after VSG over time, the proportion of neutrophils is persistently higher than in sham mice.…”
Section: Vsg Causes Bone Loss Through Mechanisms Independent Of G-csfcontrasting
confidence: 68%
“…Common metabolic abnormalities, such as obesity and metabolic syndrome, are pro-inflammatory states that can be associated with increased ESR levels ( 21 ). Moreover, in morbidly obese patients, surgically induced weight loss is associated with a marked decrease in ESR and white blood cell count, which may indicate general inflammatory status improvements ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…49 Researchers have also shown that elevated liver Mg levels may decrease ESR level in obese gastric bypass patients. 50 However, chronic kidney disease due to atherosclerosis develops cardiovascular problems. 51 Nevertheless, the results of the present study did not show the significant differences between both MgSo 4 treated groups and all control groups regarding serum level of Cr and BUN.…”
Section: Control-vr2mentioning
confidence: 99%